Pengaruh Gaya Kepemimpinan Dan Loyalitas Karyawan Terhadap Kinerja Karyawan Di Rumah Sakit Islam Hidayatullah Yogyakarta - Rita Ivana Ariyani (JMMR (Jurnal Medicoeticolegal dan Manajemen Rumah Sakit), 2016)
The background of this research is Hidayatullah Islamic Hospital (RSI) Yogyakarta and is done through leadership interferential, employee’s loyalty gives influence toward employee’s performance. (1) The phenomenon factor of harmonious relationship between leader and subordinate. (2) Factor of employee’s performance which has not yet indicating employment conduciveness. (3) Factor of employee’s loyalty toward the lack of leader’s concern on employee’s performance and opportunity to receive compensation. (4) The phenomenon of employee’s performance; the employee’s incompetence in comprehending leader’s instruction and the individual employee’s minimum responsibility which hinder the work performance. Data were compiled through interview and questionnaire, and were classified into primary and secondary data. The sample of the research consisted of 40 respondents. Method used in analyzing the data was linearity test, significance test of multiple linear regression coefficient, t test, F test, R2. The results of the research include: (1) The leader of Hidayatullah Islamic Hospital Yogyakarta doesn’t always impose sanction to its employee but instead puts trust on the head of unit to manage employee, conducts control/supervisory toward subordinate’s performance periodically in every line of work. (2) Employee’s loyalty is correlated with employee’s job and total self-image, as well as the purpose similarity between the individual and the hospital management. (3) The compatibility among willingness, achievement, and result gained is believed to create an individual with high work ethic, professionalism and commitment for its institution and also for its work achievement. The conclusions of the research are; (1) There is a positive and significant influence of leadership style toward the employee’s performance at Hidayatullah islamic hospital Yogyakarta. (2) There is a positive and significant influence of employee’s loyalty toward employee’s performance at Hidayatullah islamic hospital Yogyakarta. (3) The independent variable (leadership style and employee’s loyalty) gives positive and significant influence toward the employee’s performance at Hidayatullah Islamic hospital Yogyakarta.